2022
DOI: 10.1002/ardp.202200076
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, cytotoxicity, and molecular docking studies of novel thiazolyl–hydrazone derivatives as histone lysine acetyl‐transferase inhibitors and apoptosis inducers

Abstract: Compounds containing both thiazole and arylsulfone moieties are recognized for their high biological activity and ability to fight a variety of ailments. Thus, in this context, new derivatives of (thiazol‐2‐yl)hydrazone with an arylsulfone moiety were synthesized as CPTH2 analogs with potent anti‐histone lysine acetyl‐transferase activity. Compounds 3, 4, 10b, and 11b showed an excellent inhibitory effect on P300 (E1A‐associated protein p300), compared to CPTH2. Among all the tested derivatives, compound 10b r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 56 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…The focused library of the investigated QTHs composed of three sets Apoptosis as the mechanism of cancer cell death caused by applying various thiazolyl-hydrazones is well documented. [67][68][69][70][71] On the other hand, only two publications report that thiazolyl-hydrazones may induce cell death by autophagy. Results reported by Wang et al revealed that bromophenol-based thiazolyl-hydrazones kill cancer cells by autophagy induction.…”
Section: Discussionmentioning
confidence: 99%
“…The focused library of the investigated QTHs composed of three sets Apoptosis as the mechanism of cancer cell death caused by applying various thiazolyl-hydrazones is well documented. [67][68][69][70][71] On the other hand, only two publications report that thiazolyl-hydrazones may induce cell death by autophagy. Results reported by Wang et al revealed that bromophenol-based thiazolyl-hydrazones kill cancer cells by autophagy induction.…”
Section: Discussionmentioning
confidence: 99%
“…One of the histone‐modifying enzymes, histone acetyltransferases involve in the acetylation of specific amino acid residues; plays a vital role in pathogenesis (Parthun, 2012., Poziello et al, 2021). Literature reports suggest preclinical studies on the inhibition of histone acetyltransferases like p300/CBP and PCAF (Abbas et al, 2022; He, Wei, et al, 2021; Kopytko et al, 2021; Manzo et al, 2009). Based on mechanism‐based cellular activity, many HAT inhibitors reported are heterocycles (Baell & Miao, 2016; He, Wei, et al, 2021).…”
Section: Drugs Used For Epigenetic Therapymentioning
confidence: 99%